Transfer wiedzy z ośrodków naukowo-badawczych do przedsiębiorstw - Krzyżanowska, Krystyna; Kijek, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
This article includes a description of the level of innovativeness of Polish economy, opportunities and barriers for cooperation of enterpreneurs with scientific research centers, the assessment of the attractiveness of the support forms for business innovative activities and proposals of changes in the state innovation policy